2019
DOI: 10.1016/j.cmi.2018.08.018
|View full text |Cite
|
Sign up to set email alerts
|

Echovirus 30 detection in an outbreak of acute myalgia and rhabdomyolysis, Brazil 2016–2017

Abstract: The 2016-2017 outbreak of acute myalgia that occurred in the northeast region of Brazil can be associated with E-30. Despite the clinical manifestations, a favourable outcome was observed for all patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 13 publications
0
14
0
2
Order By: Relevance
“…Interestingly, previous work have demonstrated that the co-circulation of a high number of different NPEV types, especially those from EV-C strains, favors recombination events [4][5] as shown by the recent isolation of type 2 VDPV polioviruses from the environment and the identification of an uncommon recombinant type3/type2 Sabinrelated poliovirus in Brazil [34,35]. Moreover, multiple infections by different NPEVs have also been associated with atypical clinical presentations [7,50].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous work have demonstrated that the co-circulation of a high number of different NPEV types, especially those from EV-C strains, favors recombination events [4][5] as shown by the recent isolation of type 2 VDPV polioviruses from the environment and the identification of an uncommon recombinant type3/type2 Sabinrelated poliovirus in Brazil [34,35]. Moreover, multiple infections by different NPEVs have also been associated with atypical clinical presentations [7,50].…”
Section: Discussionmentioning
confidence: 99%
“…In general, 25% of the genome difference of enterovirus is used as the criteria for serotyping, while 15% of the genome difference is used as the criteria for genotyping; this is widely accepted for serotyping and genotyping of enterovirus, such as EV-A71, CV-A16, and CV-A6 (Brown et al, 1999;Oberste et al, 1999a,b;Mizuta et al, 2005;Zhang et al, 2010aZhang et al, , 2013Song et al, 2017). We refer to the published genotyping criteria of EV-A71, CV-A16, and CV-A6 and combined with the latest research progress of E-30 (Lema et al, 2019;Maruo et al, 2019;Mauri et al, 2019;Sousa et al, 2019). In addition to being able to better represent the E-30 sequences in the world, we also avoid the redundancy sequences of E-30 for genotyping, which leads to the confusion and divergence of enterovirus genotyping.…”
Section: Phylogenetic Analysismentioning
confidence: 99%
“…The outbreaks of E-30, which were closely associated with encephalitis, were also frequently reported in other parts of the world, including Italy, Bulgaria, France, United Kingdom, Spain, Brazil, and Korea (Cabrerizo et al, 2008;Yang et al, 2013;Mladenova et al, 2014;Holmes et al, 2016). Surprisingly, a recent report showed that E-30 was detected in an outbreak of acute myalgia and rhabdomyolysis, indicating that E-30 possibly caused severe nonneuropathic diseases and that E-30 could cause a variety of clinical symptoms (Sousa et al, 2019).…”
Section: Introductionmentioning
confidence: 95%
See 1 more Smart Citation
“…Human enteroviruses (EV) are small non-enveloped RNA viruses belonging to the picornaviridae family and are classified into four species: EV-A, B, C, and D. Although most EV infections can be asymptomatic, they are associated with a broad spectrum of clinical presentations such as hand, foot, and mouth disease, acute myalgia, herpangina, conjunctivitis, upper and lower respiratory disease and severe syndromes of the central nervous system (CNS) [1,2]. Among the most common manifestations involving the CNS, it is worth mentioning encephalitis, acute flaccid paralysis, paralytic myelitis and aseptic meningitis [1].…”
Section: Introductionmentioning
confidence: 99%